EPISTEMOLOGI TAFSIR PROFETIK: STUDI PEMIKIRAN KHĀLID AL-BĀTILĪ - Egi Tanadi Taufik; Dzalfa Farida Humaira; Ahmad Baidowi (IAT IAIN Pontianak, 2023)
Abstract The discourse of prophetic interpretations of the Qur’ān, also known as